Electropolymerization of polyaniline nanowires on poly(2-hydroxyethyl methacrylate) coated Platinum electrode - Medeiros,Maria Fernanda Xavier Pinto (2020)
Abstract A platinum electrode (Pt) was coated with poly(2-hydroxyethyl methacrylate) (PHEMA) by electrochemical polymerization using chronopotentiometry. Electropolymerization of polyaniline nanowires doped with camphorsulfonic acid (PANI:CSA) was further performed on the surface of the Pt-PHEMA electrode by cyclic voltammetry. The coated Pt-PHEMA-PANI:CSA electrode was characterized by Fourier transform infrared spectroscopy (FTIR), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and scanning electron microscopy (SEM). According to EIS, the Pt-PHEMA electrode exhibits a charge transport resistance (Rct) of 169.19 kΩ. The EIS analysis of Pt-PHEMA-PANI:CSA electrode reveals a less resistive character (Rct=1.28 Ω) than the observed for the Pt electrode coated with PANI:CSA (Rct=0.47 kΩ). As demonstrated by SEM, the Pt-PHEMA-PANI:CSA electrode has a high surface area due to the PANI:CSA nanowires embedded in Pt-PHEMA. The biocompatibility of PHEMA, allied to the electrochemical characteristics of PANI:CSA, could be useful to the development of implantable electrodes for biomedical applications.